Проблеми ціноутворення в сфері готельно-ресторанного бізнесу - Керанчук, Тетяна Львівна (My University, 2012)
В статті розглянуті актуальні проблеми розвитку підприємств готельно-ресторанного бізнесу в Україні, актуалізовані питання ціноутворення на підприемствах готельного та ресторанного бізнесу, окреслені основні проблеми при встановленні цін на послуги підприємств, обгрунтовано необхідність постановки комплексної системи управління цінами і доходами та визначено основні її структурні складові для даної категорії підприємств. Запропонована система показників KPI (key performance indicator), які дозволяють забезпечувати моніторинг основних результатів діяльності підприємств готельно-ресторанного бізнесу та формувати управлінські рішення щодо підвищення ефективності функціонування підприємств. The article describes the current problems of the hotel and restaurant industry development in Ukraine, provides with the Euro 2012 outcome analysis in the context of obtaining strategic advantages both for hotel and restaurant industry (HORECA industry) in Ukraine and for the country in general. In addition, the article deals with the hotel and restaurants industry prices updating issues. It provides with the review of the basic problems in setting prices for services companies and explains the necessity of an integrated management system in setting prices and revenues. The article also reveals the major structural components of it for this type of enterprises. Moreover, the system of indicators KPI (key performance indicator) is proposed. This system offers monitoring of the major enterprises of the hotel and restaurant industry and providing with solutions for the management efficiency improvement. The article also gives an assessment of possible future application of the main key indicators in hotel and restaurant industry while taking into account all the particularities of this business.
Keywords: ціна; стратегія ціноутворення; методи ціноутворення; готельно-ресторанний бізнес; моніторинг; ключові індикатори діяльності; цена; prices; pricing strategy; pricing methods; hotel and restaurant industry; monitoring; key performance indicator; кафедра економіки і права